Site‐specific liquefaction fragility analysis: Cloud, stripe, and incremental approaches. (29th April 2021) - Bullock, Zach; Liel, Abbie B.; Porter, Keith A.; Dashti, Shideh
Abstract: This article adapts a handful of procedures from performance‐based earthquake engineering for use in estimating the probability of liquefaction triggering. The resulting approach, defined as liquefaction fragility analysis (LFA), produces site‐specific fragility functions for liquefaction. These fragility functions incorporate site‐specific, system‐level effects not captured by existing, broader methods, but require more detailed knowledge of both the subsurface conditions and the seismic hazard at the site. LFA accounts for system‐level effects such as pore pressure migration, dynamic layer‐to‐layer interaction, and partial saturation to the extent that these phenomena can be captured in the constitutive models used in nonlinear site response analyses. Multiple approaches for selecting ground motions for LFA are discussed and illustrated using a case study of a site in Los Angeles, California. The computational expense of using LFA for probabilistic estimate of future liquefaction seismic performance is also discussed.